2013
DOI: 10.1080/07347332.2013.822049
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Dimensions of Coping in Advanced Colorectal Cancer: Implications for Patient-Centered Care

Abstract: Promoting patient-centered care from diagnosis to end of life requires a better understanding of physical, psychological, social, and spiritual coping factors in advanced cancer. Using qualitative methods, the authors explored diagnosis, care planning, and treatment experiences of individuals with metastatic colorectal cancer (N=26). The main physical factors salient to patients during all care phases included symptoms and physical functioning. Key psychological factors included persistent uncertainty and a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…At times, however, talking with loved ones was difficult, as the patients wanted to protect them from bad things. 2,24,25,29 The patients interviewed to this study selected being open about the illness, facing reality, having a sense of humour and a positive attitude to life similarly contributed substantially to the coping process, which is also in line with other studies. 26,30 Like in this study, also Wise & Marchard (2013) similarly reported that the personal resources of the patients included not only the ability to understand the meaningfulness of life, but also positive relationships and the willingness to live life to the fullest and enjoy every moment despite the illness.…”
Section: The Coping Processes Of Incurable Cancer Patientssupporting
confidence: 79%
See 2 more Smart Citations
“…At times, however, talking with loved ones was difficult, as the patients wanted to protect them from bad things. 2,24,25,29 The patients interviewed to this study selected being open about the illness, facing reality, having a sense of humour and a positive attitude to life similarly contributed substantially to the coping process, which is also in line with other studies. 26,30 Like in this study, also Wise & Marchard (2013) similarly reported that the personal resources of the patients included not only the ability to understand the meaningfulness of life, but also positive relationships and the willingness to live life to the fullest and enjoy every moment despite the illness.…”
Section: The Coping Processes Of Incurable Cancer Patientssupporting
confidence: 79%
“…In this study, the incurable cancer patients demonstrated both uncertainty about their situation and the willingness to fight the illness, which is in line with other studies. 24 As in previous studies, one of the most important coping methods for the patients was continuing the daily routines. 3,9,[25][26] The patients identified the support of friends and family as a positive, empowering factor, which is in line with the findings of many previous studies.…”
Section: The Coping Processes Of Incurable Cancer Patientsmentioning
confidence: 74%
See 1 more Smart Citation
“…Our participants resisted cancer‐related cultural taboos, like cancer is the end of life, using spiritual beliefs. Other studies showed that spirituality was a source for resilience in adapting to physical changes caused by cancer surgery and patients with cancer perceived it as a factor in living with cancer , and false beliefs about their unproductivity caused them to do their activities as they did in the past. Moreover, one research indicated that the patients worked harder as a compensation strategy to live with cancer .…”
Section: Discussionmentioning
confidence: 99%
“…It is nearly always present and even when patients are well aware of the seriousness of the disease, they never fully lose hope. Holding on to hope is a well-known strategy identified in nursing research, such as hoping to live longer and/or see a cure for the disease [36], hoping for a miracle [36,37], and hoping to be the one to beat the odds [38]. The findings in this study coincide with those of Benzein, Norberg, and Saveman [39], who showed that holding onto hope was a means of trying to find meaning, picture a better outcome, or make life easier.…”
Section: Discussionmentioning
confidence: 99%